Structural Behavior of Slender Reinforced Concrete Columns Wrapped with Fiber Reinforced Polymers Subjected to Eccentric Loads - Gad, M.A. (Institute of Electrical and Electronics Engineers Inc., 2020)
Wrapping of reinforced concrete columns with fiber reinforced polymers (FRP) is being used as a common method to enhance their behavior to resist compression loads. The present study focuses on the experimental investigation of the structural behavior of slender reinforced concrete columns wrapped with FRP subjected to eccentric loading. Four groups consisting of 11 columns were tested in addition to a reference specimen (no wrapping). These tests studied the effect of four variables on the behavior of the columns. These variables are concrete strength, slenderness ratio, wrapping angle, and the number of layers. All specimens were tested under eccentric compressive loading to failure. Test results were compared and discussed. Â© 2020 IEEE.